Medical Comorbidities in 181 Patients With Bipolar Disorder vs. Schizophrenia and Related Psychotic Disorders: Findings From a Single-Center, Retrospective Study From an Acute Inpatients Psychiatric Unit - Mariano, Antonella; Di Lorenzo, Giorgio; Jannini, Tommaso B.; Santini, Riccardo; Bertinelli, Emanuela; Siracusano, Alberto; Niolu, Cinzia (Frontiers in Psychiatry, 2021)
Introduction: Medical comorbidities (MCs) represent a significant burden in terms of more frequent hospitalizations and overall lower life expectancy among people with severe mental disorders, such as schizophrenia and related psychotic disorders (SZ) and bipolar disorder (BD). The present article aims to compare the prevalence of MCs and to examine the associated characteristics as marital status, job occupation, level of education, and living arrangements, between BD and SZ patients. Methods: One-hundred-eight-one patients with MCs (85/47% had BD and 96/53% had SZ) were recruited retrospectively from the Acute Inpatients Psychiatry Unit of Policlinico Tor Vergata, Rome, between January-2017 and December-2020. MCs were: cardiovascular diseases (CVD), bacterial infections, mycoses, viral diseases, neoplasms, musculoskeletal, respiratory tract, urological and male genital, gynecological, neurological, gastrointestinal, metabolic syndrome, nutritional, and metabolic diseases. Results: BD had more MC than SZ (36.2 vs. 28.2%, respectively, p = 0.04). CVD and metabolic MC were more common among BD (51.8 vs.34.4%; 51.8 vs.35.3%; p = 0.018; p = 0.039; respectively), while viral diseases were more frequent in SZ (13.5 vs.3.5%, p = 0.035). Hypertension was common in both psychiatric illnesses (81.8% BD vs. 65.6% SZ, p = 0.18). Obesity was the most frequent metabolic disease in both BD and SZ (75% BD vs. 73.5% SZ, p = 0.91), followed by diabetes mellitus (52.3% BD vs. 55.9% SZ, p = 0.93), metabolic syndrome (54.5% BD vs. 47.1% SZ, p = 0.67) and dysthyroidism (47.7% BD vs. 25.7% SZ, p = 0.093). After performing a binary logistic regression analysis, only two MCs showed a statistically significant association: patients with SZ had an OR of 2.01 [CI 95% (1.00–4.01)] for CVD compared to BD; on the other hand, patients with BD had an OR of 16.57 [CI 95% (3.58–76.77)] for gynecological diseases compared to SZ patients. Conclusions: MCs are common among people with severe mental illness, especially CVD and metabolic diseases, highlighting the need for a more collaborative relationship between general medical providers and psychiatrists.